Study on Consumers’ Perceived Benefits and Risks of Smart Energy System - Park, Chankook; Heo, Wan Gyu; Lee, Myung Eun (International Journal of Energy Economics and Policy, 2024)
This study explores consumer perceptions of smart energy systems, delving into both the perceived benefits and risks associated with their adoption and usage. This study addresses a crucial gap in understanding the consumer side of smart energy system implementation. Through ordinal logistic regression analysis, the study examines the relationship between various independent variables and an ordinal dependent variable represented on a Likert scale. The findings highlight a significant consumer emphasis on ’Safe Energy System Construction’ and ’Economic Benefits,’ including ’Home Energy Saving’ and ’New Profit Creation.’ However, the perceived benefits and risks are influenced by these factors and individual propensities, such as sensitivity to environmental destruction and acceptance of new technology. The study uncovers new areas of concern, exceptionally high energy consumption and the ’Uncertainty of Electricity Rates,’ which have not been extensively addressed in previous research. The conclusions drawn from this study suggest a need for balanced policy-making that fosters technological advancement while addressing consumer apprehensions about energy consumption, rate volatility, and privacy. This study contributes to the broader discourse on technology acceptance and the sustainable implementation of smart energy solutions by providing a nuanced understanding of consumer perceptions in the evolving landscape of smart energy systems.